Atomic-scale dispersion Pd-Ru nano-material catalyst, preparation method thereof and application thereof in solvent-free toluene hydrogenation reaction
By dispersing the Pd-Ru bimetallic catalyst atomically on the nanomaterial support, the problem of inactivation of traditional catalysts at high temperatures is solved, and the toluene hydrogenation reaction with low temperature, high activity and high stability is achieved, reducing the catalyst cost.
Patent Information
- Application Number
- CN202510039681.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional toluene hydrogenation catalysts are prone to inactivation of the catalyst at high reaction temperatures, and the atomic utilization rate of precious metals is low and the cost is high.
Atomically dispersed Pd-Ru nanomaterial catalyst was used to uniformly disperse the Pd-Ru bimetal on the surface of the nanomaterial support by co-precipitation method to form fully exposed Pd-Ru nanoclusters to improve the utilization rate of metal atoms.
Under mild reaction conditions, the activity and stability of the toluene hydrogenation reaction are significantly improved, the cost of the catalyst is reduced, and the high toluene conversion and high atomic utilization are achieved.
Smart Images

Figure CN119869515A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst application in liquid-phase solvent-free toluene catalytic hydrogenation, and specifically relates to an atomic-level dispersed Pd-Ru nano material catalyst and a preparation method thereof and application thereof in solvent-free toluene hydrogenation reaction. Background Art
[0002] Reducing carbon dioxide emissions is a global priority. Strict regulation of carbon dioxide emissions and investment in renewable energy are some of the mitigation strategies currently being implemented. In order to smoothly transition to low-carbon and carbon-free energy, it is necessary to find clean energy that can replace traditional fossil fuels and can be applied on a large scale. However, renewable energy is relatively restricted by geographical factors. Uncontrollable environments such as differences at different times of the day and large seasonal fluctuations affect its use in the power grid. Hydrogen energy is one of the cleaner energy sources in the existing energy system. Water is the only product obtained after the use of hydrogen energy. There is no CO2 or other waste gas generated, which can achieve absolute zero emissions and zero pollution. The development of hydrogen energy is the main way to achieve the "dual carbon" goal, and it will also be an important part of the country's future energy system.
[0003] The low density of hydrogen under ambient conditions makes its storage challenging. Hydrogen storage in liquid organic hydrogen carriers (LOHC), which has emerged in recent years, is generally liquid at room temperature and pressure compared to traditional hydrogen storage and transportation methods. It has a safer transportation method, stronger hydrogen storage capacity, and is reversible, allowing rapid hydrogenation and dehydrogenation. This hydrogen storage method can effectively reduce the cost required during hydrogen transportation and improve safety during transportation; it can effectively solve the difficulties faced by storage and transportation in the current development of the hydrogen energy industry, facilitate long-term and long-distance storage and transportation, and is conducive to the large-scale development and application of the hydrogen energy industry. Therefore, LOHC technology has a very broad development prospect. The hydrogen storage capacity of toluene / methylcyclohexane is 6.2wt.%, which is liquid at room temperature and is a good hydrogen storage system. The temperature of common toluene catalytic hydrogenation is generally carried out at a higher reaction temperature of 120-270°C. The higher reaction temperature is prone to catalyst deactivation.
[0004] Traditional toluene hydrogenation catalysts are mostly granular catalysts of precious metals, with low atomic utilization and high metal cost. Atomically dispersed fully exposed cluster catalysts retain some metallic chemical sites while having extremely high atomic utilization and uniformly dispersed active sites. They have good development prospects in the field of toluene hydrogenation and are expected to develop LOHC toluene hydrogenation atomically dispersed catalysts with high activity and high stability at low temperatures. Summary of the invention
[0005] The present invention provides an atomic-level dispersed Pd-Ru nanomaterial catalyst, a preparation method thereof, and an application thereof in a solvent-free toluene hydrogenation reaction. In the catalyst, the nanomaterial is a carrier, the noble metal Ru is a main active component, and Pd is a synergistic effect component, which bonds with defects / vacancies on the carrier to form atomic-level dispersed Pd-Ru clusters, thereby improving the utilization rate of metal atoms. The characteristic is that the Pd-Ru bimetallic catalyst is used for toluene hydrogenation reaction, and its activity is significantly higher than that of a single metal Pd catalyst and Ru catalyst. The present invention provides a nanomaterial-loaded Pd-Ru bimetallic catalyst and a preparation method thereof, which has a simple preparation method and can efficiently prepare methylcyclohexane under mild reaction conditions. Through the synergistic effect between Pd and Ru, the toluene hydrogenation performance of the catalyst is significantly improved.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] The invention discloses an atomic-level dispersed Pd-Ru nanomaterial catalyst, which consists of an active metal component and a nanomaterial carrier. The active metal component is loaded on the nanomaterial carrier. In the catalyst, the loading amount of Pd is 0.1-2.0wt.%, preferably 0.1-0.5wt.%, the loading amount of Ru is 0.1-2.0wt.%, preferably 0.4-1.0wt.%, and the particle size of the nanomaterial carrier is 5-200nm.
[0008] Furthermore, part or most of the active metal component is anchored to vacancies / defects on the nanomaterial carrier; the nanomaterial carrier is one or more of nanodiamond / graphene composite materials, nanodiamond, nanographene, nanoactivated carbon, nanosilicon dioxide, nanoaluminum oxide and nanotitanium dioxide, preferably nanodiamond / graphene composite materials.
[0009] Furthermore, the nanodiamond / graphene composite material is a core-shell structure formed by nanodiamond as the core and graphene as the shell. 3 Carbon nucleus-sp 2 The carbon shell hybrid core-shell structure has a graphene shell thickness of 0.1 to 0.5 nm and a nano-diamond / graphene composite material particle size of 5 to 10 nm.
[0010] Furthermore, in the catalyst, Pd and Ru are loaded on the carrier in the form of atomically dispersed clusters, and part or most of the Pd and Ru are loaded on the carrier in the form of Pd-Ru clusters, and the particle size of the Pd-Ru clusters is 0.5 to 2 nm.
[0011] A method for preparing an atomic-level dispersed Pd-Ru nanomaterial catalyst comprises the following steps:
[0012] (1) taking a nanomaterial carrier and dissolving it in water to form a suspension, adding an alkaline precipitant to adjust the pH to 10-11, calculating the amount of Ru metal salt and Pd metal salt according to the loading amount of Ru and Pd, adding the metal salt to the aqueous solution, stirring the reaction, separating the solid and the liquid, washing, and drying to obtain a nanomaterial-loaded Pd-Ru catalyst precursor;
[0013] (2) The Pd-Ru catalyst precursor loaded with the nanomaterial is reduced in hydrogen or a mixture of hydrogen and an inert gas, and then cooled to room temperature in an inert atmosphere to obtain an atomically dispersed Pd-Ru nanomaterial catalyst.
[0014] Furthermore, the mass of the nanomaterial carrier described in step (1) is 150-250 mg, the volume of water is 30-100 mL; the precipitant is one or more of sodium formate, sodium carbonate, sodium bicarbonate and sodium hydroxide, preferably sodium carbonate, the Pd metal salt is one or more of palladium nitrate, palladium acetylacetonate and palladium chloride, preferably palladium nitrate, the Ru metal salt is one or more of anhydrous ruthenium chloride, ruthenium acetylacetonate and ruthenium nitrate, preferably anhydrous ruthenium chloride, the reaction temperature is 80-150° C., and the reaction time is 1-2 h.
[0015] Furthermore, when the nanomaterial carrier described in step (1) is a nanodiamond / graphene composite material, the preparation method is: take 1 to 5 g of nanodiamond raw material and carry out high-temperature roasting for 3 to 6 hours in an inert atmosphere at 900-1100°C and 80-150 mL / min; the inert atmosphere is one or more of N2, He and Ar.
[0016] Furthermore, in the mixed gas of hydrogen and inert gas described in step (2), the volume content of hydrogen is 10% to 100%, the inert gas is He or Ar, the gas flow rate is 20 to 50 mL / min, the reduction time is 1 to 3 h, and the reduction temperature is 100-400°C; the gas flow rate of the inert atmosphere is 20 to 50 mL / min, and the inert atmosphere is one or more of N2, He and Ar.
[0017] The invention discloses an atomically dispersed Pd-Ru nanomaterial catalyst and its application as a catalyst in toluene hydrogenation reaction.
[0018] Furthermore, the toluene hydrogenation reaction is a solvent-free reaction, with 0.5 to 20 mL of toluene, 30 to 100 mg of catalyst, 1.2 to 2 MPa of hydrogen reaction pressure, 100 to 120° C. of reaction temperature, and 1 to 6 h of reaction time.
[0019] Furthermore, in the toluene hydrogenation reaction, the catalyst is stably used in a cycle for 3 to 6 times, and the toluene conversion rate is 99 to 100%.
[0020] The advantages of the present invention are as follows:
[0021] (1) The present invention uses a one-step co-precipitation method to evenly disperse the Pd-Ru bimetallic on the surface of the nanomaterial carrier, and provides anchoring points for the active component Pd-Ru through carrier defects / vacancies, forming fully exposed Pd-Ru nanoclusters, thereby improving the utilization rate of Pd-Ru active metal atoms, effectively preventing the aggregation of metal nanoparticles, and greatly improving the catalytic performance.
[0022] (2) The present invention regulates the catalyst performance through the synergistic effect of Pd-Ru, thereby improving the catalyst activity to a limited extent and reducing the cost of the catalyst. The preparation method is simple, the source is wide, the catalytic activity is high, and the performance is stable.
[0023] (3) The present invention uses atomically dispersed Pd-Ru nanomaterial catalysts as catalysts for hydrogenating toluene to prepare methylcyclohexane under relatively mild conditions of reaction temperature of 100-120°C and hydrogen pressure of 1.2-2MPa. Highly dispersed Pd-Ru catalysts can expose more active atoms of precious metals, improve the utilization rate of atoms, save the cost of preparing catalysts in industrial production, and have excellent atom economy. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a spherical aberration electron microscope image of the fully exposed Pd-Ru nanocluster catalyst prepared in Example 1;
[0025] Figure 2 This is the spherical aberration electron microscope image of the catalyst with 0.5 wt.% ruthenium loading prepared in Comparative Example 2. DETAILED DESCRIPTION
[0026] The present invention is described in detail below with reference to the accompanying drawings and embodiments.
[0027] In the following examples and comparative examples, the specific catalysts are represented by element symbols and English abbreviations, wherein Pd is palladium, Ru is ruthenium, NDG is nanodiamond / graphene composite material (5-10 nm), SiO2 is nanoscale silicon dioxide (30-50 nm), TiO2 is nanoscale titanium dioxide (5-10 nm), G is graphene (50-100 nm), AC is commercial activated carbon (100-200 nm), ND is nanodiamond (5-10 nm), and Al2O3 is nanoscale aluminum oxide (average particle size is 20 nm).
[0028] The preparation process of the nano-diamond / graphene composite material carrier (NDG) is as follows: a nano-diamond raw material with a particle size distribution of 5 to 10 nm is subjected to high-temperature calcination treatment to obtain a functionalized nano-diamond, namely, a nano-diamond / graphene composite material; the high-temperature calcination treatment process is as follows: 1.5 g of the nano-diamond raw material is placed in an inert atmosphere (here, Ar) at 900-1100° C. (here, 1000° C.) and 80-150 mL / min (here, 100 mL / min) for treatment for 3-6 hours (here, 4 hours), and after calcination treatment, a nano-diamond / graphene composite material is obtained, wherein the nano-diamond / graphene composite material is a core-shell structure formed by nano-diamond as a core and defect-rich graphene as a shell, and is a sp 3 Carbon nucleus-sp 2 The core-shell structure of carbon shell hybrid (the inner core structure is nanodiamond and the outer layer is a graphene shell structure), the thickness of the graphene shell is 0.1-0.5nm, and the particle size of the nanodiamond / graphene composite material is 5-10nm.
[0029] The remaining carriers were used directly after purchase.
[0030] In the nanomaterial-supported Pd-Ru catalysts used in the following examples and comparative examples, the loading amounts of Pd and Ru are calculated based on the percentage of the mass of Pd and Ru to the mass of the carrier, respectively.
[0031] Embodiment 1:
[0032] The preparation process of the catalyst in this embodiment is as follows:
[0033] Preparation of 7 different nanomaterials supported Pd-Ru catalysts
[0034] 200 mg of NDG, SiO2, TiO2, G, AC, ND, and Al2O3 nanomaterial carrier powders were respectively mixed with 30 mL of deionized water in a round-bottom flask, stirred and ultrasonicated for 30 min to form a uniform suspension, and placed in a 100°C oil bath.
[0035] Take a certain amount of palladium nitrate and mix it with anhydrous ruthenium chloride mother liquor (Pd content is 0.1wt.%, Ru content is 0.5wt.%), add deionized water to dilute to 4mL, after dilution, the concentration of palladium nitrate solution is 0.0005mol / L in palladium, and the concentration of anhydrous ruthenium chloride solution is 0.0025mol / L in ruthenium, ultrasonic dispersion, and obtain a metal precursor solution. Then use 0.25mol / L sodium carbonate solution to adjust the pH value of the above-mentioned nanocarrier suspension to 11, then add the metal precursor solution dropwise, stir and reflux for 1h, take out the flask to cool and stand for 8h, filter with suction, wash and filter the filter cake with deionized water, and put the obtained filter cake into a 60℃ vacuum drying oven for 12h, and obtain 7 kinds of Pd-Ru catalyst precursors loaded with different nanomaterials. Then place the obtained precursor in a quartz tube and reduce it in hydrogen with a flow rate of 30mL / min for 1h, and the reduction treatment temperature is 200℃. After reduction treatment, the catalyst was cooled to room temperature in 30 mL / min helium to obtain 7 different nanomaterial-supported Pd-Ru catalysts, which were 05Ru01Pd / NDG, 05Ru01Pd / SiO2, 05Ru01Pd / TiO2, 05Ru01Pd / G, 05Ru01Pd / AC, 05Ru01Pd / ND, and 05Ru01Pd / Al2O3. The spherical aberration electron microscopy image of 05Ru01Pd / NDG is shown in Figure 1 , Pd and Ru are loaded on the carrier in the form of atomically dispersed clusters. Most of the Pd and Ru are loaded on the carrier in the form of atomically dispersed Pd-Ru clusters. The blue box is the Pd-Ru cluster with a particle size of 0.5 to 1 nm. The Pd-Ru cluster has 100% atomic utilization and the clusters composed of multiple atoms can provide catalytic active sites. The sp 2 In hybrid graphene, the presence of carbon defects will destroy the lattice, causing the local electron cloud to rearrange and produce unsaturated bonds, increasing the electronic activity and chemical activity at the defect, so that the carbon defects can interact strongly with metal atoms, making it easier to capture and fix these atoms. Therefore, most of the active metal components are anchored to the vacancies / defects on the nanomaterial carrier.
[0036] Embodiment 2:
[0037] Weigh 40mg 05Ru01Pd / NDG catalyst (ruthenium atomic loading of 0.5wt.%, Pd loading of 0.1wt.%) prepared in Example 1 and add it to the 50mL inner liner of the reactor, add 2mL toluene, no reaction solvent, the reaction temperature is 100°C, H2 is charged to make the gas pressure reach 1.5MPa, stir the reaction for 1h, and continuously introduce hydrogen during the reaction process to maintain constant pressure. After the reaction, the composition of the reaction product was analyzed by gas chromatography to obtain a toluene conversion rate of 99.9%, and the reaction TOF value was 22827.8h -1(TOF is the conversion frequency, which indicates the number of catalytic reactions that occur at each active site per unit time or the number of target products generated.)
[0038] Embodiment 3:
[0039] Weigh 40mg 05Ru01Pd / SiO2 catalyst (ruthenium atomic loading of 0.5wt.%, Pd loading of 0.1wt.%) prepared in Example 1 and add it to the 50mL inner liner of the reactor, add 2mL toluene, no reaction solvent, the reaction temperature is 100°C, fill H2 to make the gas pressure reach 1.5MPa, stir the reaction for 1h, and continuously introduce hydrogen during the reaction process to maintain constant pressure. After the reaction, the composition of the reaction product was analyzed by gas chromatography to obtain a toluene conversion rate of 95.4%, and the reaction TOF value was 14731.3h -1 .
[0040] Embodiment 4:
[0041] Weigh 40mg 05Ru01Pd / TiO2 catalyst (ruthenium atomic loading of 0.5wt.%, Pd loading of 0.1wt.%) prepared in Example 1 and add it to the 50mL inner liner of the reactor, add 2mL toluene, no reaction solvent, the reaction temperature is 100°C, fill H2 to make the pressure reach 1.5MPa, stir the reaction for 1h, and continuously introduce hydrogen to maintain constant pressure during the reaction process. After the reaction, the composition of the reaction product was analyzed by gas chromatography to obtain a toluene conversion rate of 96.7%, and the reaction TOF value was 14947.6h -1 .
[0042] Embodiment 5:
[0043] 40 mg of 05Ru01Pd / G catalyst (ruthenium atomic loading of 0.5 wt.%, Pd loading of 0.1 wt.%) prepared in Example 1 was weighed and added to the 50 mL inner liner of the reactor, 2 mL of toluene was added, no reaction solvent, the reaction temperature was 100°C, H2 was charged to make the pressure reach 1.5 MPa, and the reaction was stirred for 1 hour. Hydrogen was continuously introduced during the reaction process to maintain a constant pressure. After the reaction, the composition of the reaction product was analyzed by gas chromatography to obtain a toluene conversion rate of 59.5%, and the reaction TOF value was 9217.1 h -1 .
[0044] Embodiment 6:
[0045] Weigh 40 mg of 05Ru01Pd / AC catalyst (ruthenium atomic loading of 0.5 wt.%, Pd loading of 0.1 wt.%) prepared in Example 1 and add it to the 50 mL inner liner of the reactor, add 2 mL of toluene, no reaction solvent, the reaction temperature is 100 ° C, H2 is charged to make the pressure reach 1.5 MPa, stir the reaction for 1 hour, and continuously introduce hydrogen during the reaction process to maintain a constant pressure. After the reaction, the composition of the reaction product was analyzed by gas chromatography to obtain a toluene conversion rate of 27.0%, and the reaction TOF value was 2412.3h -1 .
[0046] Embodiment 7:
[0047] Weigh 40mg 05Ru01Pd / ND catalyst (ruthenium atomic loading of 0.5wt.%, Pd loading of 0.1wt.%) prepared in Example 1 and add it to the 50mL inner liner of the reactor, add 2mL toluene, no reaction solvent, the reaction temperature is 100°C, fill H2 to make the pressure reach 1.5MPa, stir the reaction for 1h, and continuously introduce hydrogen to maintain constant pressure during the reaction process. After the reaction, the composition of the reaction product was analyzed by gas chromatography to obtain a toluene conversion rate of 20.1%, and the reaction TOF value was 2025.1h -1 .
[0048] Embodiment 8:
[0049] Weigh 40mg 05Ru01Pd / Al2O3 catalyst (ruthenium atomic loading of 0.5wt.%, Pd loading of 0.1wt.%) prepared in Example 1 and add it to the 50mL inner liner of the reactor, add 2mL toluene, no reaction solvent, the reaction temperature is 100°C, fill H2 to make the gas pressure reach 1.5MPa, stir the reaction for 1h, and continuously introduce hydrogen to maintain constant pressure during the reaction process. After the reaction, the composition of the reaction product was analyzed by gas chromatography to obtain a toluene conversion rate of 99.8%, and the reaction TOF value was 15772.3h -1 .
[0050] Embodiment 9:
[0051] Catalyst cycle stability test: Weigh 40mg 05Ru01Pd / NDG catalyst (ruthenium atomic loading of 0.5wt.%, Pd loading of 0.1wt.%) prepared in Example 1 and add it to the 50mL liner of the reactor, add 2mL toluene, no reaction solvent, the reaction temperature is 100°C, H2 is charged to make the air pressure reach 1.5MPa, stir the reaction for 1h, and continuously introduce hydrogen during the reaction process to maintain constant pressure. The above is the first catalytic reaction. After the reaction, the catalyst is separated by filtration, washed with ethanol, and directly used for the next catalytic reaction. The reaction process is the same as the first catalytic reaction described above, and this operation is repeated twice. After each reaction, the composition of the reaction product is analyzed by gas chromatography to obtain a toluene conversion rate of 99.9%, 99.5%, and 99.8%.
[0052] Comparative Example 1:
[0053] Weigh 40 mg of NDG and add it to the 50 mL inner liner of the reactor, add 2 mL of toluene, no reaction solvent, the reaction temperature is 100 ° C, H2 is charged to make the pressure reach 1.5 MPa, stir and react for 12 hours, and hydrogen is continuously introduced during the reaction process to maintain a constant pressure. After the reaction, the composition of the reaction product was analyzed by gas chromatography, no product was detected, and the toluene conversion rate was 0.
[0054] Comparative Example 2:
[0055] 1) Catalyst preparation
[0056] Referring to the preparation method of 05Ru01Pd / NDG catalyst in Example 1, the difference is that only Pd(NO3)2 (Pd content is 0.1wt%) is added to the metal precursor solution, and other operations remain unchanged to obtain a catalyst, which is recorded as 01Pd / NDG.
[0057] 2) Toluene hydrogenation to produce methylcyclohexane
[0058] 40 mg of 01Pd / NDG catalyst (Pd loading of 0.1 wt.%) was weighed and added to the 50 mL inner liner of the reactor, 2 mL of toluene was added, no reaction solvent was added, the reaction temperature was 100°C, H2 was charged to make the gas pressure reach 1.5 MPa, and hydrogen was continuously introduced during the reaction to maintain a constant pressure. After the reaction, the composition of the reaction product was analyzed by gas chromatography, and no product was detected, and the toluene conversion rate was 0.
[0059] Comparative Example 3:
[0060] 1) Catalyst preparation
[0061] The preparation method of 05Ru01Pd / NDG catalyst in Example 1 is referred to, except that only RuCl3 (Ru content is 0.5wt%) is added to the metal precursor solution, and other operations remain unchanged to obtain a catalyst, which is recorded as 05Ru / NDG. Figure 2 , the metallic Ru is uniformly dispersed on the support mainly in the form of atomically dispersed fully exposed clusters, and the red circles are Ru clusters.
[0062] 2) Toluene hydrogenation to produce methylcyclohexane
[0063] Weigh 40mg 05Ru / NDG catalyst (Ru loading is 0.5wt.%) and add it to the 50mL inner liner of the reactor, add 2mL toluene, no reaction solvent, the reaction temperature is 100℃, H2 is charged to make the pressure reach 1.5MPa, and hydrogen is continuously introduced during the reaction process to maintain a constant pressure. After the reaction, the composition of the reaction product was analyzed by gas chromatography to obtain a toluene conversion rate of 48.7% and a reaction TOF value of 4943.9h -1 .
[0064] Comparative Example 4:
[0065] Weigh 40mg 05Ru01Pd / NDG catalyst (ruthenium atomic loading of 0.5wt.%, Pd loading of 0.1wt.%) prepared in Example 1 and add it to the 50mL inner liner of the reactor, add 2mL toluene, no reaction solvent, the reaction temperature is 80°C, H2 is charged to make the pressure reach 1.5MPa, stir the reaction for 1h, and continuously introduce hydrogen during the reaction process to maintain constant pressure. After the reaction, the composition of the reaction product was analyzed by gas chromatography to obtain a toluene conversion rate of 40.7%, and the reaction TOF value was 6779.6h -1 .
[0066] Comparative Example 5:
[0067] Weigh 40mg 05Ru01Pd / NDG catalyst (ruthenium atomic loading of 0.5wt.%, Pd loading of 0.1wt.%) prepared in Example 1 and add it to the 50mL inner liner of the reactor, add 2mL toluene, no reaction solvent, the reaction temperature is 90°C, H2 is charged to make the gas pressure reach 1.5MPa, stir the reaction for 1h, and continuously introduce hydrogen during the reaction process to maintain constant pressure. After the reaction, the composition of the reaction product was analyzed by gas chromatography to obtain a toluene conversion rate of 70.6%, and the reaction TOF value was 11851.0h -1 .
[0068] Comparative Example 6:
[0069] Weigh 40mg 05Ru01Pd / NDG catalyst (ruthenium atomic loading of 0.5wt.%, Pd loading of 0.1wt.%) prepared in Example 1 and add it to the 50mL inner liner of the reactor, add 2mL toluene, no reaction solvent, the reaction temperature is 100°C, fill H2 to make the gas pressure reach 0.5MPa, stir the reaction for 1h, and continuously introduce hydrogen to maintain constant pressure during the reaction process. After the reaction, the composition of the reaction product was analyzed by gas chromatography to obtain a toluene conversion rate of 4.1%, and the reaction TOF value was 697.7h -1 .
[0070] Comparative Example 7:
[0071] Weigh 40mg 05Ru01Pd / NDG catalyst (ruthenium atomic loading of 0.5wt.%, Pd loading of 0.1wt.%) prepared in Example 1 and add it to the 50mL inner liner of the reactor, add 2mL toluene, no reaction solvent, the reaction temperature is 100°C, fill H2 to make the pressure reach 1.0MPa, stir the reaction for 1h, and continuously introduce hydrogen to maintain constant pressure during the reaction process. After the reaction, the composition of the reaction product was analyzed by gas chromatography to obtain a toluene conversion rate of 22.4%, and the reaction TOF value was 3753.6h -1 .
[0072] Comparative Example 8:
[0073] Weigh 40mg 05Ru01Pd / NDG catalyst (ruthenium atomic loading of 0.5wt.%, Pd loading of 0.1wt.%) prepared in Example 1 and add it to the 50mL inner liner of the reactor, add 2mL toluene, no reaction solvent, the reaction temperature is 100°C, H2 is charged to make the gas pressure reach 1.5MPa, stir the reaction for 0.5h, and continuously introduce hydrogen during the reaction process to maintain constant pressure. After the reaction, the composition of the reaction product was analyzed by gas chromatography to obtain a toluene conversion rate of 48.3%, and the reaction TOF value was 16004.3h -1 .
[0074] Comparative Example 9:
[0075] Weigh 40 mg of 05Ru01Pd / NDG catalyst (ruthenium atomic loading of 0.5 wt.%, Pd loading of 0.1 wt.%) prepared in Example 1 and add it to 50 mL of inner liner, add 2 mL of toluene, no reaction solvent, the reaction temperature is 100 ° C, H2 is charged to make the pressure reach 1.5 MPa, stir and react for 0.75 h, and hydrogen is continuously introduced during the reaction process to maintain constant pressure. After the reaction, the toluene conversion rate is 70.1%, and the reaction TOF value is 16030.9h -1 .
[0076] Comparative Example 10:
[0077] Weigh 20 mg of 05Ru01Pd / NDG catalyst (ruthenium atomic loading of 0.5 wt.%, Pd loading of 0.1 wt.%) prepared in Example 1 and add it to the 50 mL inner liner of the reactor, add 2 mL of toluene, no reaction solvent, the reaction temperature is 100 ° C, H2 is charged to make the pressure reach 1.5 MPa, stir the reaction for 1 hour, and continuously introduce hydrogen during the reaction process to maintain a constant pressure. After the reaction, the composition of the reaction product was analyzed by gas chromatography to obtain a toluene conversion rate of 49.2%, and the reaction TOF value was 16021.4h -1 .
[0078] Based on the above experimental results, it can be seen that the atomically dispersed Pd-Ru nanomaterial catalyst proposed in the present invention has good catalytic performance. When catalyzing the solvent-free toluene hydrogenation reaction, the reaction hydrogenation activity is significantly improved. At a reaction temperature of 100°C, a hydrogen pressure of 1.5MPa, and stirring for 1h, a toluene conversion rate of 99.9% can be obtained, and the reaction TOF value is 22827.8h -1 Moreover, the catalyst synthesis method is mature, has good stability, is easy to recycle and is environmentally friendly.
[0079] The above are preferred embodiments of the present invention, but the protection content of the present invention is not limited to the above embodiments. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are also included in the present invention.
Claims
1. An atomically dispersed Pd-Ru nanomaterial catalyst, characterized in that: The catalyst consists of an active metal component and a nano material carrier, wherein the active metal component is loaded on the nano material carrier; in the catalyst, the loading amount of Pd is 0.1 to 2.0 wt.%, preferably 0.1 to 0.5 wt.%, the loading amount of Ru is 0.1 to 2.0 wt.%, preferably 0.4 to 1.0 wt.%, and the particle size of the nano material carrier is 5 to 200 nm.
2. The atomically dispersed Pd-Ru nanomaterial catalyst according to claim 1, characterized in that: Part or most of the active metal components are anchored to vacancies / defects on the nanomaterial carrier; the nanomaterial carrier is one or more of nanodiamond / graphene composite materials, nanodiamond, nanographene, nanoactivated carbon, nanosilicon dioxide, nanoaluminum oxide and nanotitanium dioxide, preferably nanodiamond / graphene composite materials.
3. The atomically dispersed Pd-Ru nanomaterial catalyst according to claim 2, characterized in that: The nanodiamond / graphene composite material is a core-shell structure with nanodiamond as the core and graphene as the shell. 3 Carbon nucleus-sp 2 The carbon shell hybrid core-shell structure has a graphene shell thickness of 0.1 to 0.5 nm and a nano-diamond / graphene composite material particle size of 5 to 10 nm.
4. The atomically dispersed Pd-Ru nanomaterial catalyst according to claim 1, characterized in that: In the catalyst, Pd and Ru are loaded on the carrier in the form of atomically dispersed clusters, and part or most of the Pd and Ru are loaded on the carrier in the form of Pd-Ru clusters, and the particle size of the Pd-Ru clusters is 0.5-2 nm.
5. A method for preparing the atomically dispersed Pd-Ru nanomaterial catalyst according to any one of claims 1 to 4, characterized in that: The steps include: (1) taking a nanomaterial carrier and dissolving it in water to form a suspension, adding an alkaline precipitant to adjust the pH to 10-11, calculating the amount of Ru metal salt and Pd metal salt according to the loading amount of Ru and Pd, adding the metal salt to the aqueous solution, stirring the reaction, separating the solid and the liquid, washing, and drying to obtain a nanomaterial-loaded Pd-Ru catalyst precursor; (2) The Pd-Ru catalyst precursor loaded with the nanomaterial is reduced in hydrogen or a mixture of hydrogen and an inert gas, and then cooled to room temperature in an inert atmosphere to obtain an atomically dispersed Pd-Ru nanomaterial catalyst.
6. The method for preparing an atomically dispersed Pd-Ru nanomaterial catalyst according to claim 5, characterized in that: The mass of the nano material carrier in step (1) is 150-250 mg, and the volume of water is 30-100 mL. When the nano material carrier is a nano diamond / graphene composite material, the preparation method is as follows: 1-5 g of nano diamond raw material is subjected to high temperature roasting in an inert atmosphere at 900-1100° C. and 80-150 mL / min for 3-6 h; the precipitant is one or more of sodium formate, sodium carbonate, sodium bicarbonate and sodium hydroxide, preferably sodium carbonate; the Pd metal salt is one or more of palladium nitrate, palladium acetylacetonate and palladium chloride, preferably palladium nitrate; the Ru metal salt is one or more of anhydrous ruthenium chloride, ruthenium acetylacetonate and ruthenium nitrate, preferably anhydrous ruthenium chloride; the reaction temperature is 80-150° C., and the reaction time is 1-2 h.
7. The method for preparing the atomically dispersed Pd-Ru nanomaterial catalyst according to claim 5, characterized in that: In the mixed gas of hydrogen and inert gas described in step (2), the volume content of hydrogen is 10% to 100%, the gas flow rate is 20 to 50 mL / min, the reduction time is 1 to 3 hours, and the reduction temperature is 100-400° C.; the gas flow rate of the inert atmosphere is 20 to 50 mL / min.
8. Use of the atomically dispersed Pd-Ru nanomaterial catalyst according to any one of claims 1 to 4 as a catalyst in toluene hydrogenation reaction.
9. The use of the atomically dispersed Pd-Ru nanomaterial catalyst in toluene hydrogenation reaction according to claim 8, characterized in that: The toluene hydrogenation reaction is a solvent-free reaction, with 0.5-20 mL of toluene, 30-100 mg of catalyst, 1.2-2 MPa of hydrogen reaction pressure, 100-120° C. of reaction temperature and 1-6 h of reaction time.
10. The use of the atomically dispersed Pd-Ru nanomaterial catalyst according to claim 8 in toluene hydrogenation reaction, characterized in that: In the toluene hydrogenation reaction, the catalyst is stably used in a cycle for 3 to 6 times, and the toluene conversion rate is 99 to 100%.